Os jogos no ensino da matemática nos anos iniciais - Pereira, Raimundo Nonato (Universidade Federal Rural do Semi-Árido, 2020)
The present work deals with the use of concrete and digital games as a tool to support the teaching of mathematics, with the purpose of analyzing the importance of games and playful activities in the learning of mathematics, we believe that when working with diversified subjects the teacher allows children get in touch with concrete objects having to solve contextualized situations, develop the cognitive resources and the necessary skills to face the varied situations experienced by her socially. Learning in mathematics through innovative pedagogical resources can awaken the student's interest in studying the discipline. The theoretical contribution used consisted of studies by several authors and from Brazil (2013), PCNs (1st to 4th grade, 1997). For this purpose, a bibliographic research was carried out, in books, scientific articles, magazines and electronic networks and other materials of a scientific nature. These data are used in the study in the form of citations, serving as a basis for the development of the researched subject.
Keywords: Jogos matemáticos; educação matemática; ensinoaprendizagem; inovações pedagógicas; CIENCIAS EXATAS E DA TERRA::MATEMATICA